From stress signals to fertility challenges: the role of damage-associated molecular patterns in male reproduction - Cao, Heran; Liu, Shujuan; Cui, Shichao; Nie, Hua; Liu, Xiaohua; Qin, Weibing (Frontiers in Immunology, 2025)
Male infertility is influenced by genetic abnormalities, hormonal imbalances, lifestyle factors, and environmental exposures. Recently, Damage-Associated Molecular Patterns (DAMPs) have emerged as key players in male reproductive health, particularly in regulating inflammatory responses and tissue damage. This review highlights the role of critical DAMPs, such as HMGB1, HSPs, ATP, eCIRP, histones, and cfDNA, in processes like spermatogenesis, sperm maturation, and fertilization. Released through mechanisms like necrosis, apoptosis, pyroptosis, and exosomes, DAMPs significantly influence immune regulation, thereby affecting male fertility. Understanding these roles offers new therapeutic avenues targeting DAMPs to improve male reproductive health and treat infertility.